Effects of Whole SST Anomaly in the Tropical Indian Ocean on Summer rainfall Over Central Asia - Meng, Lixia; Zhao, Yong; Li, Mingang (Frontiers in Earth Science, 2021)
The effects of sea surface temperature (SST) anomaly in the tropical Indian Ocean (IO) on summer rainfall over central Asia (CA) are investigated using NCEP/NCAR reanalysis circulation data, Hadley Centre SST data, and GPCC gridded precipitation data for 1971–2016. Results show that the SST anomalies over the whole tropical IO play important roles in modulating summer rainfall over southeast CA via the subtropical westerly jet. When the SSTs in the tropical IO are in positive phases, the south Asian monsoon is weakened, which reduces summer rainfall in the Indian monsoon regions corresponding to less release of latent heat. There is an anomalous anticyclone over the Indian Peninsula and an anomalous cyclone in the upper troposphere over CA, corresponding to a shift of the tropical westerly jet farther south over CA. The southward shift of westerly jet would be responded to anomalous cyclone at 500 hPa over CA and water vapor transported into CA through two steps from the Arabian Sea, above both contribute to more summer rainfall over CA.